1994
DOI: 10.1002/cm.970270104
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of fibers and their association with talin in the cleavage furrows of PtK2 cells

Abstract: PtK2 cells of exceptionally large size were microinjected with fluorescently labeled probes for actin, myosin, filamin, and talin in order to follow the assembly of the contractile proteins into the cleavage furrows. Whereas in cells of normal size, there is usually a diffuse pattern of localization of proteins in the cleavage furrow, in these large, flat cells the labeled proteins localized in fibers in the cleavage furrow. Often, the fibers were striated in a pattern comparable to that measured in the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…By microinjection in exceptionally large cells of fluorescently labeled probes for actin, myosin, filamin, or talin, Sanger et al (1994) showed for the first time that rows of fluorescent talin are apparent as cleavage formation occurs. More recently, evidence was provided for interaction of talin with the mitotic apparatus in the Dictyostelium microorganism, because impairment of cytokinesis was observed in talin-null cells (Niewöhner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…By microinjection in exceptionally large cells of fluorescently labeled probes for actin, myosin, filamin, or talin, Sanger et al (1994) showed for the first time that rows of fluorescent talin are apparent as cleavage formation occurs. More recently, evidence was provided for interaction of talin with the mitotic apparatus in the Dictyostelium microorganism, because impairment of cytokinesis was observed in talin-null cells (Niewöhner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although in this study decompactionrecompaction was experimentally induced, it also occurs spontaneously to blastomeres of mouse embryos undergoing mitosis. Division of adherent cells is characterized by dramatic cytoskeletal rearrangements, controlled by Ca 2ϩ ions, while the cells round up and traction force appears in the furrow without relaxation of the adherent poles (52,61,62). Preimplantation mouse embryos are free entities formed by blastomeres that adhere only between themselves but not to a substratum.…”
Section: Discussionmentioning
confidence: 99%
“…Purified myosin II was labeled with tetramethylrhodamine-5 (and -6) iodoacetamide (AR-myosin II) (Molecular Probes, Junction City, OR) (DeBiasio et al, 1988;Hahn et al, 1993). AR-myosin II incorporation and distribution has been well-characterized in nonmuscle cells (DeBiasio et al, 1988;Sanger et al, 1989;Kolega and Taylor, 1993;Verkhovsky and Borisy, 1993;Sanger et al, 1994;Cramer and Mitchison, 1995), including colocalization by immunofluorescence and electron microscopy.…”
Section: Materials and Methods Fluorescent Analogues Biosensors Andmentioning
confidence: 99%
“…These tools allow the investigation of dynamic processes globally, while attaining high spatial and temporal resolution. This approach has already yielded important information about the dynamics, during cytokinesis, of actin assembly (Wang and Taylor, 1979), the recruitment of pre-existing actin filaments into the cleavage furrow (Cao and Wang, 1990a), the cortical transport of actin filaments (Cao and Wang, 1990b), the assembly and disassembly of actin and myosin IL-based fibers (Mittal et al, 1987;Sanger et al, 1989), the potential relationship between stress fibers and fibers in the cleavage furrow (Sanger et al, 1994), the global contractile activity during cytokinesis (Wang et al, 1994), and the role of myosin II in postmitotic cell spreading (Cramer and Mitchison, 1995). The dynamic changes in free [Ca2+I have been investigated, but the results have been variable (Salmon, 1989;Hepler, 1994), although recent evidence supports a direct role of free [Ca211 in cytokinesis (Fluck et al, 1991;Ciapa et al, 1994;Chang and Meng, 1995).…”
Section: Introductionmentioning
confidence: 99%